Engineering human organoid development ex vivo—challenges and opportunities. (March 2020) - Matthys, Oriane B.; Silva, Ana C.; McDevitt, Todd C.
Abstract: The rapid progress of organoid technologies is attributable to the application of developmental biology principles, but organoid methods need further refinement provided by engineering approaches. However, we must first begin with common consensus on the critical features that distinguish organoids from simpler microtissues that lack the cellular complexity, structure, and function that organoids can achieve. Furthermore, current abilities to derive organoids from stem cells or multipotent progenitors favor certain germ lineages and tissue types more so than others, although the full reasons for this imbalance have yet to be determined. Technical challenges remain to identify the critical starting parameters for organoid reproducibility, systematically manipulate the proportions of differentiated cells from progenitors, and comprehensively characterize cell phenotypes spatially using advanced transcriptomic and 3D imaging methods. Advances in these regards will undoubtedly improve the robustness and predictability of existing organoids and permit the creation of organoids that have yet to be described. Graphical abstract: Image 1 Highlights: Consistent criteria must be used to describe and distinguish 'organoids.' Current research reveals bias toward ectoderm- and endoderm-derived organoid models. Limited control of organoid starting conditions impedes reproducibility.